2019
DOI: 10.1029/2019gl082562
|View full text |Cite
|
Sign up to set email alerts
|

Active‐Passive Surface Water Classification: A New Method for High‐Resolution Monitoring of Surface Water Dynamics

Abstract: This study develops a new, highly efficient method to produce accurate, high‐resolution surface water maps. The “active‐passive surface water classification” method leverages cloud‐based computing resources and machine learning techniques to merge Sentinel 1 synthetic aperture radar and Landsat observations and generate monthly 10‐m‐resolution water body maps. The skill of the active‐passive surface water classification method is demonstrated by mapping surface water change over the Awash River basin in Ethiop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…Sentinel-1 data in GEE is only processed through primary processing such as noise removal, calibration and geocoding. As we all know, layover and shadow will bring some errors to the extraction of water based on radar images [17]. In this study, compositing ascending and descending SAR scenes have reduced this error but do not fully eliminate it.…”
Section: Uncertainty Of This Studymentioning
confidence: 80%
See 2 more Smart Citations
“…Sentinel-1 data in GEE is only processed through primary processing such as noise removal, calibration and geocoding. As we all know, layover and shadow will bring some errors to the extraction of water based on radar images [17]. In this study, compositing ascending and descending SAR scenes have reduced this error but do not fully eliminate it.…”
Section: Uncertainty Of This Studymentioning
confidence: 80%
“…Some studies have shown that synthetic ascending and descending SAR scenes reduce some errors caused by radar shadows or layover, but do not completely eliminate them [17]. Using optical sensors to detect surface water will also encounter the problem of terrain shadows, and there has been a lot of research performed using slope dataset to solve this problem [6,11,27,28].…”
Section: Development Of Different Water Masksmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Landsat imagery has been leveraged to identify not only the location of the world's waterbodies but also their sizes and dynamics. Previous efforts to map global inland waters fall into two categories: 1) vector-based mapping, which provides static polygons of the world's lakes and lacks any temporal dynamics [5][6][7][8][9] , and 2) raster-based mapping, which divides the Earth's surface into pixels and documents the change in the presence of water over time in those pixels [10][11][12][13][14][15][16] . Both these categories of approaches provide an incomplete view of the world's lakes in that the former does not indicate the dynamic nature of surface water, and the latter tracks the presence of water at the level of pixels but fails to associate these pixels with lakes.…”
Section: Background and Summarymentioning
confidence: 99%
“…Most recently, Slinski et al . (2019) developed a new method, called as active‐passive water classification method, to map surface water dynamics and applied it to the Awash River Basin in Ethiopia that has freshwater lakes, saline water lakes and reservoirs between years 2014 and 2017. Year 2015 was a term during which the basin experienced a major East African regional drought, whereas; localized flood events were highly noticeable in 2016.…”
Section: Introductionmentioning
confidence: 99%